Solve this

Question:

$2 x^{2}-\sqrt{3} x+1=0$

Solution:

Given:

$2 x^{2}-\sqrt{3} x+1=0$

Solution of a general quadratic equation $a x^{2}+b x+c=0$ is given by:

$x=\frac{-b \pm \sqrt{\left(b^{2}-4 a c\right)}}{2 a}$

$\Rightarrow x=\frac{-(-\sqrt{3}) \pm \sqrt{(-\sqrt{3})^{2}-(4 \times 2 \times 1)}}{2 \times 2}$

$\Rightarrow x=\frac{\sqrt{3} \pm \sqrt{3-8}}{4}$

$\Rightarrow x=\frac{\sqrt{3} \pm \sqrt{-5}}{4}$

$\Rightarrow \quad x=\frac{\sqrt{3} \pm \sqrt{5} i}{4}$

$\Rightarrow \quad x=\frac{\sqrt{3}}{4} \pm \frac{\sqrt{5}}{4} i$

Ans: $x=\frac{\sqrt{3}}{4}+\frac{\sqrt{5}}{4} i$ and $x=\frac{\sqrt{3}}{4}-\frac{\sqrt{5}}{4} i$

 

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now